1966
DOI: 10.1111/j.1365-2141.1966.tb00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Gastric Parietal Cell Antibody in Families of Patients with Iron Deficiency Anaemia

Abstract: There is an association of pernicious anaemia with iron deficiency anaemia (Faber and Gram, 1924). There is also a high incidence (85 per cent) of gastric parietal cell antibody in the sera of patients with pernicious anaemia (Taylor, Roitt, Doniach, Couchman and Shapland, 1962) and a less marked, but significantly increased incidence (33 per cent) in patients with iron deficiency anaemia who have a histamine fast achlorhydria (Dagg, Goldberg, Anderson, Beck and Gray, 1964). Pernicious anaemia has a familial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1966
1966
1987
1987

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Although they are very common in frank and latent pernicious anaemia (Wright et al, 1966) there is no proof that these antibodies cause gastritis, and it is possible that they are produced as a reaction to mucosal damage, the result of iron deficiency (Markson and Moore, 1962;Moulton, 1964) or of other factors (Edwards and Coghill, 1966). MacFadyen, Goldberg, Dagg, and Anderson (1965) found a significant history of bleeding only among those iron-deficient patients with both achlorhydria and antibodies who did not have relatives with antibodies. The equally low incidence of parietal-cell antibodies in patients who had had partial gastrectomy for duodenal ulcer and in others with gastric carcinoma has also suggested that antibodies may be a reaction to gastritis, but that few patients are able to produce them (Kravetz, van Noorden, and Spiro, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Although they are very common in frank and latent pernicious anaemia (Wright et al, 1966) there is no proof that these antibodies cause gastritis, and it is possible that they are produced as a reaction to mucosal damage, the result of iron deficiency (Markson and Moore, 1962;Moulton, 1964) or of other factors (Edwards and Coghill, 1966). MacFadyen, Goldberg, Dagg, and Anderson (1965) found a significant history of bleeding only among those iron-deficient patients with both achlorhydria and antibodies who did not have relatives with antibodies. The equally low incidence of parietal-cell antibodies in patients who had had partial gastrectomy for duodenal ulcer and in others with gastric carcinoma has also suggested that antibodies may be a reaction to gastritis, but that few patients are able to produce them (Kravetz, van Noorden, and Spiro, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…This observation has been pursued by investigating the incidence of gastric antibody in 76 relatives of six of the patients with latent pernicious anaemia and in 72 relatives of five of the patients without latent pernicious anaemia. Ten of the 76 relatives of the latent-pernicious-anaemia propositi possessed the gastric antibody in their serum, but only two of the 72 relatives of propositi without latent pernicious anaemia possessed the gastric antibody, a difference which is statistically significant (P<0.05) (McFadyen et al, 1966). Te Velde et al (1964) found the gastric antibody in 20% of a large group of relatives of patients with pernicious anaemia compared with 6 % in a control series.…”
Section: Discussionmentioning
confidence: 94%
“…Existing observations suggest that iron deficiency and its consequent anaemia may result in pathological changes in gastric mucosa including gastritis and gastric atrophy which in turn may lead to reduced secretion of gastric acid (Davidson and Markson, 1955; Badenoch, Evans and Richards, 1957) but Valberg, Taylor, Witts and Richards (1961) were unable to find any significant pathological change in gastric mucous membranes of iron deficient rats. The most striking reduction in gastric acid has been observed in those patients described as having idiopathic microcytic hypochromic anaemia with circulating antibodies to parietal cells (Shearman, Delamore and Gardner, 1966; Dagg, Goldberg, Anderson, Beck and Gray, 1964;MacFadyen, Goldberg, Dagg and Anderson, 1965). Patients with iron deficiency anaemia due to blood loss and without circulating antibodies to parietal cells have shown lesser degrees of hypochlorhydria (Shearman et al, 1966;Dagg et al, 1964).…”
mentioning
confidence: 99%